Insights of Phaseolus vulgaris’ response to infection by Uromyces appendiculatus using an RNA-seq approach - Makhumbila, Penny; Rauwane, Molemi; Muedi, Hangwani; Figlan, Sandiswa (Frontiers in Plant Science, 2025)
Rust, caused by the obligate biotrophic fungal pathogen Uromyces appendiculatus (Pers.:Pers.) Unger, is one of the most destructive diseases of common bean (Phaseolus vulgaris L.) causing yield losses in production areas worldwide. This study explores the use of RNA sequencing (RNA-seq) as a breeding prediction tool through the assessment of gene expression patterns of common bean susceptible (Golden Gate Wax) and resistant (Teebus-RR-1) varieties to U. appendiculatus virulent strain race 31-1 at two time points (14- and 21- days post infection; dpi). U. appendiculatus induced stress-responsive genes such as heat shock proteins (HSPs: HSP17.6II and ATHSP22.0), receptor-like kinases (RLKs: CRK29), cytochrome monooxygenases (CYP76C4, CYP82C4 and CYP94B1) and terpene synthases (TPS21 and TPS14) at 14-dpi, while BIA and WRKY70 transcription factors, among others were regulated differentially in both varieties at 21-dpi. Genes RPS2, CAR1 and DM2H were among the identified potential biomarkers associated with U. appendiculatus resistance. Enrichment of signaling receptor activity, response to stress, sesquiterpenoid and triterpenoid biosynthesis, and plant hormone signal transduction were unique to Teebus-RR-1. Overall, the findings of this study indicate varying gene expression patterns between varieties in response to U. appendiculatus. Insights provided by the RNA-Seq approach used in this study on mechanisms of P. vulgaris’ response to U. appendiculatus can be used for biomarker discovery and possible development of resistant varieties.